Lengthy complex lumbar fusion surgery in high-risk elderly patient under spinal anesthesia: A case report. (2019) - Curto, Ryan A.; Edwards, Charles C.; Lin, Charles; Brown, Charles H.
Highlights: The longest reported lumbar surgery in an elderly patient under spinal anesthesia. Spinal Anesthesia is a feasible option for lengthy geriatric lumbar surgery. SA affords effective anesthesia with possibly lower physiological stress to some older patients. Spinal Anesthesia may have elongated efficacy in the elderly population. Abstract: Introduction: Spinal Anesthesia (SA) continues to be an emerging technique for lumbar fusion surgery in the elderly population. SA is an appealing option in the high-risk geriatric population for several reasons, including the potential for reduced systematic stress, reduced blood loss, and reduced post-operative delirium. The safe limits of spine surgery under SA remain undetermined. Presentation of case: The following case-study describes an elderly high-risk patient (ASA III) with severe spinal stenosis and degenerative scoliosis who presented with lower back and right leg pain and underwent a 3-level lumbar fusion surgery with spinal anesthesia. The procedure lasted 3 h and 44 min with sufficient anesthesia maintained throughout. The patient experienced minor post-operative complications, but had an excellent clinical outcome at 3-month follow-up. Discussion: Further research should be conducted to define the temporal limits of SA in elderly patients and the etiology of post-operative complications following lumbar fusion surgery under spinal anesthesia in the geriatric population. Conclusion: The case reported, herein, demonstrates the feasibility of SA in elderly patients undergoing lengthy complex lumbar surgeries who have been designated "high-risk" patients (ASA > II) and provides support for future investigation into surgical and anesthesia treatment options for geriatric high-risk patients presenting with complex lumbar spine pathologies.